2019
DOI: 10.1002/pbc.28064
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive mediators of adaptive functioning outcomes in survivors of pediatric brain tumors treated with proton radiotherapy

Abstract: Background: Cranial radiotherapy (RT) is associated with risk for cognitive and adaptive dysfunction. Proton RT (PRT) is a technique hypothesized to spare cognition by reducing exposure to non-target brain tissue. However, little is known regarding functional outcomes in survivors of pediatric brain tumor (BT) treated with PRT. The present study examined the relationship between cognitive and adaptive outcomes in pediatric BT survivors post-PRT.Methods: Survivors treated with either focal (n = 33) or craniospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…20,21 In a recent report, PRT was associated with more favorable outcomes (compared with XRT) in most neurocognitive domains in children with medulloblastoma. 22,23 In addition to the dose and volume dependence previously noted, RT doses to specific regions of the brain, particularly the temporal lobes and hippocampi, may disproportionally affect long-term IQ and academic performance. 16,24,25 RT-induced injury of the brain's white matter may partially explain these cognitive changes as magnetic resonance imaging (MRI) studies have correlated a decline in cognitive ability with white matter loss.…”
Section: Clinical Significancementioning
confidence: 99%
“…20,21 In a recent report, PRT was associated with more favorable outcomes (compared with XRT) in most neurocognitive domains in children with medulloblastoma. 22,23 In addition to the dose and volume dependence previously noted, RT doses to specific regions of the brain, particularly the temporal lobes and hippocampi, may disproportionally affect long-term IQ and academic performance. 16,24,25 RT-induced injury of the brain's white matter may partially explain these cognitive changes as magnetic resonance imaging (MRI) studies have correlated a decline in cognitive ability with white matter loss.…”
Section: Clinical Significancementioning
confidence: 99%
“…1 Radiation treatment is a life-saving intervention that can be associated with neurocognitive, emotional, and behavioral sequalae, [2][3][4][5][6][7] although the use of proton radiation treatment (PRT) has yielded more favorable outcomes due to its dose-sparing properties. [8][9][10] Many studies examining the outcomes of PRT revealed cognitive and adaptive functioning in the normal range more than 3 years post-treatment; [11][12][13] however, adaptive functioning challenges at 5 years post-PRT have been observed, with greater vulnerability in survivors treated with craniospinal irradiation (CSI). 12 Studies of psychosocial and executive functioning outcome following PRT in pediatric brain tumor survivors are relatively recent, and require replication to strategically guide intervention.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Many studies examining the outcomes of PRT revealed cognitive and adaptive functioning in the normal range more than 3 years post-treatment; [11][12][13] however, adaptive functioning challenges at 5 years post-PRT have been observed, with greater vulnerability in survivors treated with craniospinal irradiation (CSI). 12 Studies of psychosocial and executive functioning outcome following PRT in pediatric brain tumor survivors are relatively recent, and require replication to strategically guide intervention. Challenges with social functioning have been described, 14 most notably in aspects of peer exclusion and isolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence suggests that cognitive skills may act as mediators between clinical variables and AF in pediatric patients with acquired brain injury (ABI) [ 7 , 11 , 12 , 13 ], but research on the cognitive predictors of AF in pediatric BT patients is scarce.…”
Section: Introductionmentioning
confidence: 99%